Determinant of palm oil demand: the case of Malaysia / Abdah Aliff Amir - Amir, Abdah Aliff (Faculty of Plantation and Agrotechnology, 2018)
It has been a concern that European Parliament has voted overwhelmingly to boycott the utilization of palm oil in all European biofuels by 2020, referring to ecological concerns. This study re-examines the trend analysis of the factors that affecting the palm oil export in Malaysia during the period of 1986 until 2016 by employing Vector Error Correction Model (VECM). The annual data series that was used in the study is crude palm oil price, soybean oil price, and finally exchange rate. The Phillips-Perron root test shows that at level, all the series are non-stationary. In the 1st difference, palm oil export, crude palm oil price, soybean oil price, and exchange are stationary. The Johansen co-integrating approach shows that the presence of co-integrating relationship in the model. The findings shows that in the long run, crude palm oil prices have a significant effect on the palm oil export in Malaysia. However, the short run indicates that only exchange rate influence the palm oil export. In conclusion, a suggestion can be made which is increasing activities in the production and processing of palm oil-based products by foreign firms so that it can encourage the increase in the export demand for palm oil.